THE EFFECT OF ALLOXAN-INDUCED HYPERGLYCEMIA ON THE RENAL CORTEX - Sofia Frolova; Olena Gordienko; Olha Yarmolenko (Eastern Ukrainian Medical Journal, 2022)
About 422 million people in the world suffer from diabetes mellitus. Among diseases, diabetes ranks third, and among endocrine disorders, it ranks first. Some issues concerning the pathogenesis of this disease are unclear. The main reason for diabetes damage is high blood glucose levels. Hyperglycaemia has a toxic effect on the vessels of the kidneys. The present study aims to investigate the impact of alloxan-induced diabetes mellitus on the remodeling of the renal cortex. Materials and methods. We divided twenty-four mature white male rats into the control and experimental groups. We administered alloxan to experimental animals intraperitoneally at a single dose of 40 mg/kg. Blood glucose levels were measured 2, 12, and 24 hours after injection of alloxan and then weekly. The average glucose level remained 11.0 ± 2.0 mmol/l. Animals were sacrificed on days 14, 21, and 45. We stained histological preparations of kidneys with hematoxylin and eosin. The selected dose of alloxan and the method of its administration caused persistent hyperglycemia in rats and did not lead to their death. Results. On the 14th day, the diseased kidney had a thickening of the glomerular capillary walls. Nephrons had a spherical shape with a slightly uneven surface. On the 21st day of the observation, it was more difficult to distinguish the cortex from the medulla. On the 45th day, the distal tubules lost their usual shape, became thinner, and were difficult to distinguish from other tubules by histological preparation. The cortex became spongy due to cystic dilation of the tubules. Conclusions. All components of the renal cortex underwent daily changes. At the early stages of the experiment, it looked much denser compared to the cortical layer of the kidneys of animals in the control group. The number of subcapsular nephrons visually increased, and the renal capsule thickened. In the later period of the experiment, dilatation and blood fullness of glomerular capillary with their leukocyte infiltration were observed. In addition, there was a cystic expansion of the tubules, due to which the cortical layer of the kidney looked like a sponge.